The use of Short Messaging System (SMS) as knowledge dissemination and learning tools: A case of Open University Malaysia (OUM) - Safie, Nurhizam (2006)
The objective of the research is to investigate the effectiveness usages of Short Messaging System (SMS) as a knowledge dissemination and learning tool in Open University Malaysia (OUM). The focus is on the project called mySMS, a service provide to the learners in the September Semester 2005. This pilot project will involve 50 learners. Learners who are registered under Management Information Systems, Strategic Information Systems and Human-Computer Interaction courses shall involve as participants in this project. SMS services which will be provided to learners are as follows :- multiple choice questions with feedback, pre and post self -test, quizzes and assignment notification, crucial assignment reminders, access to examination and test marks, fact of the week, web links, reading material lists, course schedule and calendar as well as access to financial statements and courses registration.